The Effect of Increasing Plant Density on Performance and Heterobeltiosis in Maize Testcrosses among 23 Inbreds and Three Testers - , A. M. M. Al-Naggar; , R. Shabana; , M. S. Hassanein; , T. A. Elewa; , A. S. M. Younis; , A. M. A. Metwally (Archives of Current Research International, 2017)
Information on the heterosis of maize germplasm is essential in maximizing the effectiveness of hybrid development. The objectives of the present study were to assess the effects of elevated plant density on mean performance and heterobeltiosis and to identify the best testcrosses in these parameters. A set of 23 inbred lines of maize, were top-crossed to three testers to produce 69 testcrosses. Inbreds, testers, testcrosses and five commercial cultivars were evaluated in the field under three plant densities using a split plot design with three replications. Elevating plant density from 47,600 (low density; LD) to 71,400 (medium density; MD) and 95,200 (high density; HD) plants/ha caused a significant reduction in grain yield/plant (GYPP), and its components, leaf angle, penetrated light at ear and chlorophyll concentration index (CCI) and significant increase in grain yield/ha (GYPH), days to anthesis, anthesis silking interval, and plant height. Increasing the plant density increased average heterobeltiosis in eight traits, namely GYPH, GYPP, 100 kernel weight, rows/ear, tassel branch number, tassel dry weight and CCI. The best testcrosses in heterobeltiosis for GYPH (L28 x Sd7 and L21 x Sd7 under HD and IL51 x Giza2, IL84 x SC10 and L28 x SC10 under HD and MD) were also the best crosses in per se performance for GYPH under respective environments. These crosses could be useful in future breeding programs for improving plant density tolerance in maize.